Prognostic implications of ventricular fibrillation in acute myocardial infarction: new strategies required for further mortality reduction. Issue 3 (1st September 2000) - Sayer, J W; Archbold, R A; Wilkinson, P; Ray, S; Ranjadayalan, K; Timmis, A D
Abstract : OBJECTIVE: To determine the changing risk of ventricular fibrillation, the prognostic implications, and the potential long term prognostic benefit of earlier hospital admission, after acute myocardial infarction. DESIGN: Prospective observational study. SETTING: A district general hospital in east London. PATIENTS: 1225 consecutive patients admitted to a coronary care unit with acute myocardial infarction. MAIN OUTCOME MEASURES: Time of onset of pain and ventricular fibrillation, and long term survival of patients admitted with acute myocardial infarction. RESULTS: The rate of ventricular fibrillation in these hospital inpatients was high in the first hour from onset of pain (118 events/1000 persons/h; 95% confidence interval (CI) 50.7 to 231) and fell rapidly to an almost constant low level by six hours; 27.4% of patients with early ventricular fibrillation died in hospital, compared with 11.6% of those without (p < 0.0001), but mortality in patients who survived to hospital discharge was not altered by early ventricular fibrillation (five year survival: 75.0% (95% CI 60.0% to 84.8%) with ventricular fibrillation v 73.3% (95% CI 69.6% to 76.6%) without ventricular fibrillation). CONCLUSIONS: Patients successfully resuscitated from early ventricular fibrillation have the same prognosis as those without ventricular fibrillation after acute myocardial infarction. Faster access to facilities for resuscitation must be achieved if major improvements in the persistently high case fatality of patients after acute myocardial infarction are to be made.